Evaluation of radial nerve palsy treatment: tendon transfer with the flexor carpi radialis combination - Sarker, Abu Zaker Hossain; Hossain, Sayed Nadir; Siddique, Zillur Rahman; Kader, Abdul; Paul, Rajib; Chakma, Subal Jyoti; Roy, Milon Kumar; Moktaruzzaman,; Hossain, Sazzad; Sarker, Uday Kumar (International Surgery Journal, 2023)
Introduction: Radial nerve palsy, a common peripheral nerve injury, significantly impacts the quality of life of affected individuals. The standard treatment is tendon transfer, but the optimal choice of tendon transfers remains a subject of ongoing debate. This study aimed to evaluate the treatment of radial nerve palsy through tendon transfer with the flexor carpi radialis combination in a Bangladeshi population. Methods: This observational study was conducted over 18 weeks at the Department of Orthopedic Surgery of 3 medical college hospitals in Bangladesh. Forty adult patients with radial nerve palsy were selected based on specific inclusion criteria. Participants were evaluated preoperatively and postoperatively using the Disabilities of the Arm, Shoulder, and Hand (DASH) score. Complications were also recorded. Results: The majority of participants were male (77.5%) and had right-sided injuries (72.5%). The most common cause of injury was humerus shaft injury (55.0%). The most common site of injury was middle third of the humerus shaft (67.50%). Postoperatively, 85.0% achieved an "Excellent" grade. Complications were minimal, with 90% of participants experiencing no complications. Conclusions: Tendon transfer with the flexor carpi radialis combination appears to be an effective treatment for radial nerve palsy, with significant improvements in DASH scores postoperatively and minimal complications. Further research is needed to confirm these findings and compare the effectiveness of this treatment with other tendon transfer combinations.